Kryzys systemu komunistycznego w Polsce lat osiemdziesiątych - Dudek, Antoni (Pamięć i Sprawiedliwość, 2007)
The article depicts six main reasons, for which the crisis of the communist system in Poland in the eighties escalated. The most important factor were changes in the USSR after Mikhail Gorbachov’s accession to power and proclamation of “perestroyka”, the consequence of which was withdrawal from the Brezhnev doctrine. Among the internal factors the most important were: condition of the economy, which after the introduction of martial law was in the constant crisis; the phenomena of privatisation of the communist state, which in the last period of the PZPR rule led to the process of bestowing property on some people from the governing apparatus of the communist Poland; deregulation of the political system, the most important manifestation of which was impairment of the PZPR position, which had a hegemonic role in the political system of the communist Poland; evolution of mood of the public, which after 1985 became much lower; activities of hierarchy of the Catholic Church and political opposition, the main part of which belonged to the moderate stream seeking agreement with WojciechJaruzelski’s team.